Second Sight : Biennial IV - Beal, Graham W.J.; Hopkins, Henry T. (San Francisco : San Francisco Museum of Modern Art, 1986)
Albert, Hermann ; Allington, Edward ; Armajani, Siah ; Brown, Roger ; Fritzius, Harry ; Higgins, Douglas ; Hollowell, David ; Komar and Melamid ; Le Brun, Christopher ; Mariani, Carlo Maria ; McCoy, Ann ; McKenna, Stephen ; Nerdrum, Odd ; Paolini, Giulio ; Staley, Earl ; Stanley, M; Louise ; Steir, Pat ; Stuart, Michelle ; Tansey, Mark
Second Sight : Biennial IV, San Francisco Museum of Modern Art, San Francisco, 21 September - 16 November 1986
boek